The magic of middle school musicals [ inspire your students to learn, grow, and succeed - Bobetsky, Victor V. (Rowman & Littlefield Education, 2009)
Bobetsky begins with advice on how to select a musical, obtain copyright permission, and arrange the music for middle school voices. He discusses strategies for teaching the music in the choral classroom, auditioning, casting, and rehearsal procedures. Practical suggestions show directors how to work with student actors, create choreography, and manage scenery, set design, costumes, lighting, and more. --from publisher descriptioin.